FINANCIAL FLOWS AND ENVIRONMENTAL SUSTAINABILITY IN NIGERIA: ENVIRONMENTAL KUZNETS HYPOTHESIS - Ariyibi, Mayowa Ebenezer; Ilo, Bamidele Muzliu; Yinusa, Ganiyu Olumuyiwa (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2025)
Introduction: This study examines the effect of financial flows (external and internal) on environmental sustainability in Nigeria, testing the environmental Kuznets hypothesis. Methods: The study employed secondary data sourced from the Central Bank Statistical Bulletin and World Development indicator. The period of the inquiry was from 1991 to 2022, both years inclusive. The study employed the auto-regressive distributed lag to determine the short and long-run relationship between the outcome variables and explanatory variables. Results: The findings revealed that external debt, net export and government expenditure on education has a positive significant effect on CO2 emission. Foreign direct investment, foreign aid and tax revenue have a negative significant effect on CO2 emission. It is therefore concluded that external debt and net export channeled through capital project and improvement in receipt from export would increase the units in per capital income of the populace, which in the short-run would increase the level of CO2 emissions in Nigeria. Conclusion and suggestion: It recommended that government should develop policies and incentives that would attract foreign direct investment in green industries and technologies, ensure foreign companies adhere to environmental regulations and standards in the recipient country.